Pengaruh Pemasaran Hijau dan Kesadaran Lingkungan Serta Dampaknya terhadap Perilaku Konsumen Hijau – Study Usia Remaja - Santoso, Radityo; Setiawati, Rahmi; Fatimah, Siti (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The increase in population leads to an increase in the needs of the community, which results in companies increasing production levels in order to meet the increasing demand for community needs. Various companies currently still rely on raw materials for products that come from nature, this results in the exploitation of nature to meet these increasing needs. This exploitation results in environmental pollution and damage so that the environment is damaged as a negative result of the production process that is less concerned about the sustainability of nature. In response to the negative impacts caused by the exploitation of the production process and also products that are less environmentally friendly, many consumers have shifted their decision to buy environmentally oriented products. Based on the results of this study, it was found that green marketing has an influence on consumer behaviour. Green labelling variables, green product variables, premium, and price variables, consumer trust in the environment have an influence on consumer behaviour.